Structural properties of hydrogenated amorphous silicon (A-SI:H) thin film grown via radio frequency plasma enhanced chemical vapor deposition (RF PECVD) - Anthony Hasbi, Hasbullah (2005)
An investigation of the structural properties of hydrogenated amorphous silicon (a-Si:H) thin films prepared by plasma enhanced chemical vapour deposition of silane (SiH4) was done using a combination of atomic force microscopy (AFM), photoluminescence, infrared and UV spectroscopy. Films were prepared with rf power ranging from 100-250 W. For every rf power employed, substrate temperature were varied from room temperature to 300Â°C. The deposition rate was found to be slightly increasing with an increase of rf power while decreasing as the substrate temperature increases. The AFM images can be classified into three groups: most smooth (rms: 1.2nm), intermediate rms (2.4-3.6 nm) and highest roughness (rms: 4.9 nm). The transition to rougher films at higher substrate temperature is attributed to a change in the deposition process. The IR vibrational spectra obtained from FTIR spectroscopy display modes which can be characterized as predominantly hydrogen motions. On the basis of these identifications, it is found that samples produced on high-temperature have SiH, SiH2 and (SiH2)n groups with very little SiH3. In contrast, the ir spectra of samples produced on room-temperature are dominated by vibrational modes of SiH3 and (SiH2)n. At low rf power, the spectrum is dominated by a strong absorption bands at 2000 cm-1 associated with SiH stretching bond and also 630 cm-1 associated with SiH bending. At high rf power, an additional absorption band at around 2090 cm-1 which corresponds to (SiH2)n stretching mode and SiH2 stretching mode becomes more pronounced. The optical energy gap obtained from UV spectroscopy decreases with increasing of rf power and substrate temperature. This decrement is due to the drop of hydrogen content. At low substrate temperature, photoluminescence spectrum of a-Si consists of a relatively broad band with its main peak around 1.4 eV. The spectrum shifts to lower energies (around 1.37 eV) and its intensity decreases with increasing temperature. It is suggested that this is due to an activated non-radiative recombination (relaxation) process where exciton are captured by deep traps and this become more probable as temperature increases.